Effectiveness of Coach Training Programs in Turkey (According to 1994 and 2002 Different Regulations) - SUNAY, Hakan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
Sports trainers, which are called sports trainers, have an important place in the development of sports. Therefore, the effectiveness of the training programs implemented in coach training is important, but the effectiveness of the 15-20 day courses conducted by the sports training department, where today a fairly large coach potantiel is grown, is at the top of the topics discussed by the public in the sport. The purpose of this research: sports education in Turkey is being implemented by the head coach of the circle to determine the effectiveness of training programs and make recommendations to the activity carried out more such programs. The research is a descriptive survey model. The data were obtained from the questionnaires from the trainers who participated in the training programs of different sports branches. Survey; It was prepared by the researcher in order to determine the opinions of coaches trained according to the coaching training regulations established in 1987, 1994 and 2002 on the effectiveness of the coaching training programs. The universe of the research; Graduated from the training programs opened by the Department of Sports Education, the General Directorate of Sports Services (GDSS) is approximately 5,459 coaches from 24 sports branches according to the 1994 regulation and approximately 79,896 coaches from 16 different sports branches from 60 federations according to the 2002 regulation. The sample of the research is 286 coaches who have been trained in coaching courses according to 1987 and 1994 coaching regulations and 705 coaches in total from 419 of 16 sports branches according to 2002 regulations. The data were obtained from the trainers who participated in the training courses between 1990-1995 and 2008-2018. Data, frequency and percentages were determined and then the difference between expected and observed values was analyzed by chi-square test. As a result, it was found out that the coaches perceive the goals of the training programs implemented by the GDSS differently and their expectations from the program were different and the programs were found to be insufficient in terms of physical facilities and duration.